Representasi Makna Ganda (Homograf) dalam Bahasa Makassar : Studi Linguistik pada Masyarakat di Kelurahan Pattenne Kecamatan Polong Bangkeng Selatan Kabupaten Takalar - Muhammad Saeful; Desy Ayu andhirah (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to identify and analyze the forms of homographs found in the Makassar language as used by the community in Pattene Village. This study also aims to describe how the multiple meanings of the homographs are represented in the context of everyday communication, and how the understanding of the meaning is influenced by the situation, intonation, and social relations between speakers. This study uses a qualitative approach with a descriptive method. This approach was chosen to study and describe in depth the linguistic phenomenon of multiple meanings (homographs) in the Makassar language based on data obtained from native speakers in Pattene Village. The focus of the study is directed at the use of homographs in oral communication among the community, as well as the context that influences changes in their meaning. The main data sources in this study are community speech recorded through interviews, participatory observations, and documentation of everyday conversations. The results of the study show that the community in Pattene Village uses a number of homograph words in the Makassar language that have multiple meanings depending on the context of the speech. A total of 12 main homographs were successfully identified through interviews and field observations. These homographs have the same phonological structure but show different meanings based on situational context, tone of voice, and position in a sentence. For example, the word